1994
DOI: 10.1111/j.1600-0714.1994.tb01117.x
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus DMA in oral squamous cell carcinomas and normal mucosa

Abstract: Human papillomavirus (HPV) infections in oral carcinomas and normal oral mucosa were studied by consensus primer screening and typing for HPV types 6/11, 16 and 18 DNA. After polymerase chain reaction (PCR) the DNA species of interest were identified by Southern blot hybridization with digoxigenin-labeled oligonucleotide probes. Frozen tissue and scrapings were equally suitable for HPV testing and yielded high HPV detection rates in carcinomas. By comparison, HPV analysis of paraffin-embedded material was much… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
67
1
9

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(85 citation statements)
references
References 41 publications
8
67
1
9
Order By: Relevance
“…33 Thus, other agents, such as viruses, are being investigated. 34 In particular, with regard to viral involvement, it is still highly controversial whether HR HPV can be considered an etiologic or a malignant risk factor in oral carcinogenesis: 14 some research groups 14,35,36 have identified HR HPV antigens and viral DNA in potentially malignant and malignant oral lesions, and others have defined HR HPV as playing an important role in OSCC, especially in the absence of common oral habits. 37 Historically, evidence of the carcinogenic role of HR HPVs is based on 2 oncoproteins: HPV-E6, which promotes degradation of the p53 tumor-suppressor gene product, 38 and HPV-E7, which modifies pRb tumor-suppressor gene product function, leading to increased cell proliferation and contributing to carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…33 Thus, other agents, such as viruses, are being investigated. 34 In particular, with regard to viral involvement, it is still highly controversial whether HR HPV can be considered an etiologic or a malignant risk factor in oral carcinogenesis: 14 some research groups 14,35,36 have identified HR HPV antigens and viral DNA in potentially malignant and malignant oral lesions, and others have defined HR HPV as playing an important role in OSCC, especially in the absence of common oral habits. 37 Historically, evidence of the carcinogenic role of HR HPVs is based on 2 oncoproteins: HPV-E6, which promotes degradation of the p53 tumor-suppressor gene product, 38 and HPV-E7, which modifies pRb tumor-suppressor gene product function, leading to increased cell proliferation and contributing to carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent comprehensive study, Sidransky and co-workers reported a low rate of HPV in oral SCC (12% of cases) (Gillison et al, 2000). However, other studies have reported different frequencies (Ostwald et al, 1994;Snijders et al, 1996). HPV etiology for oral cancer may be better evaluated with improvements in the detection of different types of HPV.…”
Section: Loh In Verrucous Lesionsmentioning
confidence: 99%
“…Apesar da exposição da mucosa oral a vários carcinógenos, somente um pequeno percentual dos indivíduos desenvolvem câncer 1 . Lembrando que a carcinogênese é um processo multifatorial, a mutagênese é determinada também por agentes co-carcinogenéticos como o papilomavírus humano (HPV) 2,3 . O epitélio da cavidade oral e orofaringe é uma membrana mucosa com propensão para o desenvolvimento neoplásico, sendo exposto a vários carcinógenos nutricionais e ambientais, determinantes de lesões decorrentes de efeitos da infecção pelo HPV e mutagênese química, sendo que dos 77 tipos de HPV isolados, 41 deles apresentam maior tropismo pelas mucosas.…”
Section: Introductionunclassified
“…Isto ocorre a partir da síntese de três oncogens (oncoproteínas), sendo que a E5 estimula o fator de crescimento epidérmico (FCE), a E6 ligada ao p53 selvagem e a E7 ao Rb selvagem, todas encontradas nos HPV de alto risco (HPV16,18,31,33,35,39,42) para a mucosa oral 2,4 . Quanto à investigação do HPV humano como agente etiológico do CEC da boca e orofaringe, o mesmo foi detectado em lesões pré-malignas do trato genital feminino, onde predominou o mesmo tipo de neoplasia em localização anatômica sujeita a traumas e infecções contínuas 3 . Dentre os 77 HPV humanos (pequenos DNA vírus), os HPV 6 e 11 são encontrados nas doenças benignas e os HPV 16 e 18 são vírus de alto risco por estarem ligados em 30% com neoplasias malignas humanas 5 .…”
Section: Introductionunclassified